Age, growth and maturation of the brown surgeonfish Acanthurus nigrofuscus at Okinawa-jima Island, Japan - Toshida, Harumi; Fukuchi, Ifue; Nakamura, Yohei; Tachihara, Katsunori (Ichthyological research, 2024)
Acanthurus nigrofuscus (Acanthuridae), a common fish on the coral reefs of the Ryukyu Islands, southern Japan, is considered to be important for maintaining the health of coral reef ecosystems. However, the life history of the species in Japan is largely unknown. In this study, age, growth and maturation of A.